The Future of Leadership: Integrating AI Technology in Management Practices - Loso Judijanto; Asfahani Asfahani; Nova Krisnawati (Edujavare Publishing, 2022)
With the rapid advancement of artificial intelligence (AI) technology, organizations face a paradigm shift in leadership and management practices. This research aims to explore the integration of AI technology in leadership, focusing on its impact, challenges, and opportunities. This research uses a systematic literature review (SLR) method; this research synthesizes existing knowledge and identifies key findings regarding the role of AI in decision-making, ethical considerations, organizational readiness, and required leadership skills. These findings highlight the potential benefits of AI in improving decision-making processes and organizational efficiency while emphasizing the importance of addressing ethical issues, improving organizational readiness, and developing new leadership competencies. This research contributes to understanding the future leadership landscape in AI technology integration.